Comparative Experiences of EFL Students Using Gamified Versus Traditional Web-Based Grammar Practice: A Qualitative Case Study - Baidawi, Achmad; Rabi'ah, Rabi'ah; Habibullah, Mosleh; Virdyna, Nina Khayatul (PANYONARA: Journal of English Education, 2025)
The increasing use of digital tools in English as a Foreign Language (EFL) instruction has transformed grammar learning, offering contrasting affordances. This study explored how university-level EFL students in Indonesia experience gamified (Quizizz) versus traditional web-based grammar platforms. Adopting a qualitative case study with 30 participants, data were collected through classroom observations and semi-structured questionnaires based on 15 behaviorally anchored indicators aligned with three research questions. Findings revealed that Quizizz heightened engagement through competitive elements, immediate feedback, and peer interaction—though some learners experienced stress due to time constraints. In contrast, traditional grammar websites promoted self-paced study, detailed explanations, and conceptual clarity, albeit with lower interaction and occasional disengagement. Cross-platform comparison showed learners valued both tools: Quizizz for motivational drill practice and traditional platforms for in-depth understanding and exam preparation. These insights suggest that neither platform alone is universally optimal. A blended instructional approach, combining gamified engagement with structured guidance, offers a more balanced grammar learning experience tailored to diverse learner preferences. Future research should include longitudinal and comparative designs across proficiency levels and integrate theoretical perspectives such as Self-Determination Theory and the Technology Acceptance Model to further elucidate learners' motivation and platform use.